2005
DOI: 10.1523/jneurosci.2122-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Platelet-Derived Growth Factor-α Receptor-Mediated Tyrosine Kinase Activity as a Cellular Mechanism for K+-Channel Regulation during Oligodendrocyte DevelopmentIn Situ

Abstract: Oligodendrocyte maturation has been defined based on expression of developmentally regulated antigens. However, transitions at early stages of the lineage have not been functionally characterized fully in situ. Combining 2Ј,3Ј-cyclic nucleotide 3Ј-phosphodiesterase (CNP)-promoter driven enhanced green fluorescent protein expression and whole-cell capacitance measurements permitted a reliable distinction between subcortical white matter NG2 ϩ oligodendrocyte progenitors (OPs) and O4 ϩ preoligodendrocytes (pre-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 45 publications
4
29
0
Order By: Relevance
“…We demonstrated that, in the CNP-EGFP mouse, expression of O4 in white matter regions corresponds to a postmitotic stage of the oligodendrocyte lineage (Chittajallu et al, 2005). These findings are further supported by our analysis in cultured OPCs, demonstrating that (1) Sox17 protein levels increase during the morphological conversion of bipolar OPCs to multipolar preoligodendrocytes, and (2) Sox17 immunoreactivity is significantly higher in O4 ϩ preoligodendrocytes that in OPCs or oligodendrocytes.…”
Section: Discussionsupporting
confidence: 83%
“…We demonstrated that, in the CNP-EGFP mouse, expression of O4 in white matter regions corresponds to a postmitotic stage of the oligodendrocyte lineage (Chittajallu et al, 2005). These findings are further supported by our analysis in cultured OPCs, demonstrating that (1) Sox17 protein levels increase during the morphological conversion of bipolar OPCs to multipolar preoligodendrocytes, and (2) Sox17 immunoreactivity is significantly higher in O4 ϩ preoligodendrocytes that in OPCs or oligodendrocytes.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, endothelin-1, an extremely powerful vasoconstrictor that is involved in vascular remodeling, has been shown to inhibit KCNK3 via Rho kinase in human PASMCs. [41][42] Growth factor signaling, such as PDGF receptor and tyrosine kinase activity, act via a common pathway that influences the function and expression of K + channels [43][44] and could also partially explain the decrease in I KCNK3 . Moreover, downstream of the PDGF or tyrosine kinase receptors, Src kinase signaling is crucial for K + channel function, including TASK1/KCNK3.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to whole-cell recording of currents, series resistances values ranged between 4 to 12 MΩ and were compensated by at least 75%. Delayed rectifying (K DR ) and transient (K A ) potassium currents were isolated as previously described (Chittajallu et al, 2004; Chittajallu et al, 2005). Biocytin/NG2 and biocytin/O4 staining was performed as previously described (Chittajallu et al, 2005).…”
Section: Methodsmentioning
confidence: 99%